Herbal Medicine in the Treatment of Non-Alcoholic Fatty Liver Diseases-Efficacy, Action Mechanism, and Clinical Application - Xu, Yu; Guo, Wei; Zhang, Cheng; Chen, Feiyu; Tan, Hor Yue; Li, Sha; Wang, Ning; Feng, Yibin (Frontiers in Pharmacology, 2020)
Non-alcoholic fatty liver disease (NAFLD) is a common chronic liver disease with high prevalence in the developed countries. NAFLD has been considered as one of the leading causes of cryptogenic cirrhosis and chronic liver disease. The individuals with obesity, insulin resistance and diabetes mellitus, hyperlipidaemia and hypertension cardiovascular disease have a high risk to develop NAFLD. The related critical pathological events are associated with the development of NAFLD including insulin resistance, lipid metabolism dysfunction, oxidative stress, inflammation, apoptosis and fibrosis. The development of NAFLD range from simple steatosis to non-alcoholic steatohepatitis (NASH). Hepatic steatosis is characterized by fat accumulation, which represents the early stage of NAFLD. Then, inflammation triggered by steatosis drives early NAFLD progression into NASH. Therefore, the amelioration of steatosis and inflammation is essential for NAFLD therapy. The herbal medicine have taken great effects on the improvement of steatosis and inflammation for treating NAFLD. It has been found out that these effects involved the multiple mechanisms underlying lipid metabolism and inflammation. In this review, we pay particular attention on herbal medicine treatment and make summary about the research of herbal medicine, including herb formula, herb extract and naturals compound on NAFLD. We make details about their protective effects, the mechanism of action involved in the amelioration steatosis and inflammation for NAFLD therapy as well as the clinical application.